1995
DOI: 10.2307/1592404
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Optimum Formulation of a Novel Infectious Bursal Disease Virus (IBDV) Vaccine Constructed by Mixing Bursal Disease Antibody with IBDV

Abstract: A novel vaccine against infectious bursal disease virus (IBDV) has been developed. The new vaccine was constructed by mixing bursal disease antibody (BDA) contained in whole antiserum with live IBDV before lyophilization. To establish various formulations of BDA and IBDV, several BDA doses between 5 units and 80 units of BDA/50 microliters were mixed with 100 EID50/50 microliters of IBDV suspension in Expt. 1; in Expt. 2, several IBDV doses between 10 EID50/50 microliters and 977 EID50/50 microliters of IBDV s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…The economic impact of clinical and sub-clinical IBD warrants the search and use of efficient vaccines and vaccination strategies to match changes in the field situation for effective control of IBDV (Whitfill et al, 1995;Pitcovski et al, 2003;Yong-Chang et al, 2005;Lazarus et al, 2008;Le Gros et al, 2009). In Nigeria, most vaccines used for the control of IBDV as well as the virus seed for local vaccine production are imported (Okeke & Tanimu, 1982), leading to frequent vaccination failures in the field (Abdu et al, 2001) due to antigenic differences between local strains and vaccine strains (Owoade et al, 2004;Adamu et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…The economic impact of clinical and sub-clinical IBD warrants the search and use of efficient vaccines and vaccination strategies to match changes in the field situation for effective control of IBDV (Whitfill et al, 1995;Pitcovski et al, 2003;Yong-Chang et al, 2005;Lazarus et al, 2008;Le Gros et al, 2009). In Nigeria, most vaccines used for the control of IBDV as well as the virus seed for local vaccine production are imported (Okeke & Tanimu, 1982), leading to frequent vaccination failures in the field (Abdu et al, 2001) due to antigenic differences between local strains and vaccine strains (Owoade et al, 2004;Adamu et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…These VN rAb, however, when mixed with Bv and inoculated either in ovo, 1-day-old or 2-week-old chicks, formed an Icx and delayed replication of Bv. The effectiveness of the rAb Icx was similar to the Icx formed by polyclonal anti-IBDV sera (Whitfill et al , 1995;Jeurissen et al ., 1998). Immunohistological staining for IBDV following inoculation of rAb8.IBDV and rAb34.IBDV complexes to 18-day-old embryos indicated that virus replication in bursa was delayed for 5 to 7 days in comparison with IBDV-inoculated chicks; IBDV release from the Icx was completed by 10 d.p.i., and virus replication was resolved by day 14.…”
Section: Discussionmentioning
confidence: 58%
“…In the study of Jeurissen et al . (1998) hyperimmune sera was used in an Icx at a dilution of 1:10, whereas in the study of Whitfill et al . (1995) it was not clear what dilution of sera would represent 24 antibody units.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first time that the promise has existed to prevent, treat, and cure endogenous ag induced mishaps in humans specifically and without side effects. The study of the affects of injection of ag:ab ICs at different ratios is not new, nor is the use of ICs in increasing ab production (Klaus, 1978;Kunkl & Klaus, 1981;Nie et al, 1997;Stoner et al, 1975;Stoner & Terres, 1963;Terres et al, 1972;Terres & Stoner, 1962;Terres & Wolins, 1959;Terres & Wolins, 1961) and even in vaccination (Haddad et al, 1997;Jeurissen et al, 1998;Whitfill et al, 1995;Xu et al, 2005;Yao et al, 2007). So far most of the pertinent investigations have described the role that ag:ab ICs play in immune response upon injection of such complexes at various ratios, and how enhanced ab production occurs during primary and secondary ab responses (Barabas et al, 2007d;Heyman, 2000;Stoner & Terres, 1963;Xu et al, 2005;Yao et al, 2007).…”
Section: Mvt For the Prevention And Cure Of Diseases Caused By Chronimentioning
confidence: 99%